2023
DOI: 10.1111/ans.18465
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the COVID‐19 pandemic on lung cancer surgery in Queensland

Abstract: Background: The coronavirus disease-19 (COVID-19) pandemic poses unprecedented challenges to global healthcare. The contemporary influence of COVID-19 on the delivery of lung cancer surgery has not been examined in Queensland. Methods: We performed a retrospective registry analysis of the Queensland Cardiac Outcomes Registry (QCOR), thoracic database examining all adult lung cancer resections across Queensland from 1/1/2016 to 30/4/2022. We compared the data prior to, and after, the introduction of COVID-restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, it is notable that as the pandemic waned, things gradually returned to normal, with early stages enjoying a significant increase in proportions, accounting for 48.9% of T2–T4 stages. This discrepancy between the pandemic and post-pandemic periods has been observed worldwide [ 17 , 18 ]. Kato et al [ 19 ] reported a significant shift in the distribution of stage I diseases during the pandemic, with a notable decrease in stage IA1 cases and a substantial increase in stage IA3 and IB incidences compared to previous years.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, it is notable that as the pandemic waned, things gradually returned to normal, with early stages enjoying a significant increase in proportions, accounting for 48.9% of T2–T4 stages. This discrepancy between the pandemic and post-pandemic periods has been observed worldwide [ 17 , 18 ]. Kato et al [ 19 ] reported a significant shift in the distribution of stage I diseases during the pandemic, with a notable decrease in stage IA1 cases and a substantial increase in stage IA3 and IB incidences compared to previous years.…”
Section: Discussionmentioning
confidence: 96%
“…The decrease in the number of surgeries has been reported globally, with a hospital in the US also reporting a decrease of 50.4% compared to the previous period [ 17 ]. Significant differences have been evidenced in Queensland [ 18 ], as well as in countries such as Japan [ 19 ], Sweden [ 20 ], or England [ 21 ], where a significant decline in the number of surgical interventions performed has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations